Pole frazeosemantyczne "gniew" w języku polskim (na materiale polskiej frazeologii kinematycznej) = Phraseosemantic Field "Anger" in the Polish language (based on kinematic Polish phraseology) - Łozińska, Oksana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the nuclear and peripheral structure of the phraseo-semantic field (hereafter PSF) "anger" that is formed by kinematic phraseological units (hereafter PU). The data for the study have been 93 kinematic PU to denote anger, the prototype of which is a corresponding mimic sign (63 PU), a gesture (9 PU) or a significant movement of the body (21 PU).
Keywords: pole frazeosemantyczne; kinematyczny związek frazeologiczny; znak mimiczny; gest; znaczący ruch ciała; aspekty znaczenia frazeologizmu; phraseosemantic field; kinematic phraseological units; mimic sign; gesture; significant movement of the body; aspects of meaning